Analysis of Implementation of SMEs Tax Enforcement: The effects of tax justice dimensions, understanding of tax accounting on SME’s tax compliance - Christina Tri Setyorini; Dewi Susilowati (Universitas Hayam Wuruk Perbanas, 2018)
The purpose of this study was to determine the effect of understanding on tax accounting, tax justice toward tax compliance on SMEs tax. The research method applied in this study is quantitative deductive method. The population taken were SMEs registered in Department of Cooperatives SMEs, Trade and Industry in Banyumas, Purbalingga and Cilacap. The data were collected by using convenience sampling. They were collected through questionnaires and semi-structured interviews with 115 SMEs. The finding shows that the SMEs tax compliance is influenced by understanding on tax accounting and tax justice. In addition, this study also reveals that the majority of SMEs have lack of understanding about tax accounting and most respondents still doubt about tax justice. Thus, the recommendation of this research is to conduct a judicial review of Government Regulation No. 46 Year 2013 to conform to the principle of tax fairness, transparency in the field of taxation should be improved, and the bottom-up approach must be conducted prior to issuing regulations by the government, especially given the economic capacity of SMEs.